Effectiveness Online Learning at Biology Subject in Student’s Perception at Senior High School at Muko Muko - Irwandi Irwandi; Merri Sri Hartati; Puji Dwi Lestari (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Indonesian government tried to made many policies in covid – 19 pandemic. For example, Social distancing in big Scale (PSBB), Work From Home (WFH) and other policy in all of aspect included of education. So that learning activity did by internet online in many platforms. This research aimed to knew  how to student’s perception  and effectiveness in online learning at Biology Subject  in Senior High schools at Ipuh, Muko - Muko. The types of research was Qualitative descriptive  that described student’s perception in used whatsApp at Biology Learning by online. The data collection technique in this study used a questionnaire. This data was description about student’s perception toward used WhatsApp in Biology learning as learning media in covid – 19 pandemic. Its data was took from observation, Questionnaire and interview. Data was taken by Google form application and shared in Whatsapp group. Its Data was analyzed by descriptive. The conclusion of this research was student’s perception in biology learning by using WhatsApp as media during the Covid 19 pandemic showed negative respons.